Preparing for scaling: A study on founder role evolution - Van Lancker, Evy; Knockaert, Mirjam; Collewaert, Veroniek; Breugst, Nicola (Journal of Business Venturing, 2023)
One of the major entrepreneurial challenges faced by scaling firms involves changing their internal organization. Our study focuses on a particular aspect of internal organizing—namely, how founder roles evolve in preparation for scaling. By means of an in-depth case study and a combination of data collection methods, we study the evolution of formal and informal founder roles. For both types of roles, we identify a founder-driven and an interaction-driven phase, during which founder and/or joiner role-crafting take place. Through both types of role-crafting, founder roles are (re)shaped. Particularly unique to our study is that we identify three scaling-specific paths through which the role-crafting of joiners shapes founders' roles. Specifically, founders experience a role efficiency increase as they take over some of the joiner-introduced role behaviors, or a role set decrease as joiners take over some of their (formal or informal) roles. We further point to the importance of psychological safety and value fit for successful joiner role-crafting to occur and for founder roles to change following founder-joiner interactions. Our study adds to the literatures on scaling and entrepreneurship as well as to role theory and role-crafting literature.